Microfluidic anodization of aluminum films for the fabrication of nanoporous lipid bilayer support structures - Bhattacharya, Jaydeep; Kisner, Alexandre; Offenhäusser, Andreas; Wolfrum, Bernhard (Beilstein Journal of Nanotechnology, 2011)
Solid state nanoporous membranes show great potential as support structures for biointerfaces. In this paper, we present a technique for fabricating nanoporous alumina membranes under constant-flow conditions in a microfluidic environment. This approach allows the direct integration of the fabrication process into a microfluidic setup for performing biological experiments without the need to transfer the brittle nanoporous material. We demonstrate this technique by using the same microfluidic system for membrane fabrication and subsequent liposome fusion onto the nanoporous support structure. The resulting bilayer formation is monitored by impedance spectroscopy across the nanoporous alumina membrane in real-time. Our approach offers a simple and efficient methodology to investigate the activity of transmembrane proteins or ion diffusion across membrane bilayers.
Keywords: anodization; lipid bilayer; microfluidics; nanofabrication; nanoporous alumina